GRAMMATICAL PROBLEMS OF TRANSLATION ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2025)
This article examines the grammatical problems encountered in translation, highlighting the complexities that arise due to differences in syntax, morphology, and sentence structure between the source and target languages. It examines how grammatical inconsistencies can lead to misinterpretation, loss of meaning, and stylistic inconsistencies. These include tense and aspect, conjugation, word order, the use of articles, and prepositions. Ultimately, it emphasizes the importance of a deep understanding of the grammatical system in order to achieve accurate and meaningful translations.